Tourism potential of industrial and scientific sites in the context of cultural citizenship and museum communities - Roman N. Abramov (Управление культурой)
Industrial tourism has emerged as a significant facet of commercial tourism, serving as a means of engaging with industrial heritage, a resource for sociocultural revitalization of regions, and a technology for corporate communications with various stakeholders. However, the concept of industrial tourism is imprecise and constrains the resources related to industrial heritage, encompassing the histories and modernity of factories, mines, quarries, engineering structures, abandoned military sites, and scientific institutions. The practices of culturally engaging with engineering and scientific materiality extend far beyond their understanding in the «touristic dimension» and relate to the phenomenon of cultural citizenship, particularly in mono-industrial cities where science, industry, and engineering identities are vital to their inhabitants. This article examines how the industrial past and present attract external audiences to relevant locations and facilitate their development into tourist clusters. Conversely, it emphasizes the importance of integrating this heritage into the cultural everyday life of cities and the regions housing industrial sites, engaging local audiences as representatives of local cultural citizenship. The focus is on how the industrial and scientifictechnical heritage of cities can be more actively incorporated into sociocultural circulation with participation from residents and visitors, as well as the challenges and barriers encountered in this process. The article draws on synthesized interview materials and participant observations from a collective project supported by the Russian Science Foundation titled «Cultural Citizenship and Local Solidarity: Experiences in Social Inclusion of Museum Audiences in Russia.» Case studies include micro-expeditions in Nikolsk (Penza Region) and Elektrostal (Moscow Region). The problematic nature of industrial past and present in cities outside conventional tourist routes is highlighted by researchers who note that in situations of marginalization (as seen in Nikolsk), industrial spaces become stagnant in an uncertain state, «as if falling out of time, lingering indefinitely with unclear prospects.» To revitalize these spaces as tourist centers or creative industry clusters, additional efforts and, importantly, resources are required, which are more readily available in cities with operational factories. Overall, both cases illustrate that for industrial cities with intriguing industrial heritage to become attractive to tourists and reconstruct their communities in the context of cultural citizenship, a constellation of factors is necessary-ranging from resource foundations provided by functioning factories to the willingness of key actors, including museums, local governments, businesses, and local historians, to take action. Museums can play a crucial role in this reconstruction due to their neutral status and strong ties to both past and present.